2021
DOI: 10.3390/jof7080663
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic Acid and Its Hydroxylated Derivatives Suppress Early Blight of Tomato (Alternaria solani) via the Induction of Salicylic Acid Biosynthesis and Enzymatic and Nonenzymatic Antioxidant Defense Machinery

Abstract: Tomato early blight, caused by Alternaria solani, is a destructive foliar fungal disease. Herein, the potential defensive roles of benzoic acid (BA) and two of its hydroxylated derivatives, ρ-hydroxybenzoic acid (HBA), and protocatechuic acid (PCA) against A. solani were investigated. All tested compounds showed strong dose-dependent fungistatic activity against A. solani and significantly reduced the disease development. Benzoic acid, and its hydroxylated derivatives, enhanced vegetative growth and yield trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 75 publications
1
36
0
Order By: Relevance
“…One of the previous studies found that the application of benzoic acid and its hydroxylated derivatives upregulated salicylic acid-binding protein (SABP2) and pathogenesis-related protein (PRB1-2) gene expressions and reduced A. solani disease severity [61]. Therefore, we investigated the modes of action of FytoSol and INA on SABP2 and PRB1-2 gene expressions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…One of the previous studies found that the application of benzoic acid and its hydroxylated derivatives upregulated salicylic acid-binding protein (SABP2) and pathogenesis-related protein (PRB1-2) gene expressions and reduced A. solani disease severity [61]. Therefore, we investigated the modes of action of FytoSol and INA on SABP2 and PRB1-2 gene expressions.…”
Section: Discussionmentioning
confidence: 96%
“…Although INA is an analog of the SA, it does not trigger any changes in SA levels unlike the exogenous application of SA [43]. However, other SA-analog; benzothiadiazole (BTH), and benzoic acid applications increased SA levels and induced resistance against EB [35,61], providing insight into the uniqueness of each elicitor for plant protection. Related to these findings, FytoSol and INA applications did not upregulate the expression of PRB1-2 (Figure 4A), one of the pathogenesis-related-like proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternaria solani , a typical necrotrophic pathogen, is the main causal agent of early blight, which is a destructive foliar disease that affects potato, tomato and other cultivated Solanum species [ 1 , 2 ]. The typical disease symptoms are dark brown to black lesions with concentric rings on the leaves, which result in leaf browning and drop in severe cases.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic carboxylates such as benzoic acid have been shown to inhibit or kill microorganisms (i) by interfering with the permeability of the microbial cell membrane, causing uncoupling of both substrate transport and oxidative phosphorylation, (ii) by disruption of intracellular pH homeostasis and (iii) specific inhibition of various enzyme activities [23]. Moreover, defense priming with protective effects against early blight (Alternaria solani) in tomato has also been reported for exogenous application of benzoic acid [29].…”
Section: Introductionmentioning
confidence: 99%